Los Angeles Dodgers 5 vs Atlanta Braves 2 at Dodger Stadium - Watkins, Howard::::::::: (1987)
Dodger pitcher #57 Sean Hillegas finishing pitch to Atlanta Braves batter; Dodger #10 at shortstop Viewed from centerfield